(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the relationship between ENT disorders and cognitive decline in elderly individuals in Mirpur, AJK. Study Design: cross-sectional study Place and Duration of Study: This study was conducted at the Department of Community Medicine & ENT of DHQ Hospital & Medical College, Mirpur AJK from 1st October 2023 to 30th March 2024. Methods: A cross-sectional study was thoroughly conducted involving 200 elderly participants from outpatient clinics in Mirpur, AJK. Comprehensive ENT evaluations were carefully performed to diagnose disorders such as hearing loss, tinnitus, and chronic rhinosinusitis. Cognitive function was systematically assessed using the Mini-Mental State Examination (MMSE). Data on demographic characteristics, comorbidities, and lifestyle factors were extensively collected. Statistical analysis, including Pearson correlation and multivariate regression, was rigorously used to assess the association between ENT disorders and cognitive decline. Results: Hearing loss was predominantly identified as the most common ENT disorder, affecting 63% of participants, followed by tinnitus (36%) and chronic rhinosinusitis (21%). Cognitive decline (MMSE score <24) was noted in 48% of participants. A significant correlation between hearing loss and cognitive decline was strongly found (r=0.59, p<0.001), with a higher risk evidently observed in participants experiencing moderate-to-severe hearing loss (OR=3.4; 95% CI: 2.2–5.7). Tinnitus was also significantly associated with cognitive decline (OR=2.1; 95% CI: 1.2–3.3), while a weaker association was relatively observed with chronic rhinosinusitis (OR=1.3; 95% CI: 0.9–2.3). Conclusion: ENT disorders, particularly hearing loss and tinnitus, are strongly associated with cognitive decline among the elderly in Mirpur, AJK. Early detection and management of these disorders may help mitigate the risk of cognitive impairment, emphasizing the need for integrated care strategies in aging populations.